2010
DOI: 10.1097/yco.0b013e32833a51ce
|View full text |Cite
|
Sign up to set email alerts
|

The role of early parental bonding in the development of psychiatric symptoms in adulthood

Abstract: Current available data indicate that parent-child relationships may prevent or promote the development of psychiatric symptoms, mainly anxiety and depressive symptoms. In order to investigate the quality of parental bonding and its correlation with the level of psychological well being or psychiatric morbidity, further longitudinal studies with larger samples and adequate follow-up periods should be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 18 publications
(15 reference statements)
2
35
0
2
Order By: Relevance
“…Healthy bonding between parents and children is essential for effective functioning, but data show that disruptions in the bonding process are linked to a variety of disturbances in adult functioning. In a recent review, for example, Lima, Mello, and de Jesus Mari (2010) found that neglect, parental control, and intrusiveness in early childhood may be risk factors for the development of depressive and anxious symptoms in adulthood. These findings coincide with an earlier review which found that rejection and control were related to later anxiety and depression (Rapee, 1997).…”
Section: Specificity Of Parental Bonding and Rumination In Depressivementioning
confidence: 99%
“…Healthy bonding between parents and children is essential for effective functioning, but data show that disruptions in the bonding process are linked to a variety of disturbances in adult functioning. In a recent review, for example, Lima, Mello, and de Jesus Mari (2010) found that neglect, parental control, and intrusiveness in early childhood may be risk factors for the development of depressive and anxious symptoms in adulthood. These findings coincide with an earlier review which found that rejection and control were related to later anxiety and depression (Rapee, 1997).…”
Section: Specificity Of Parental Bonding and Rumination In Depressivementioning
confidence: 99%
“…Conversely, disrupted parental bonding, often defined as lower levels of care (rejection and neglect) and overprotection (controlling and intrusive behaviors), has been linked with the development of psychopathology (Enns et al 2002). In particular, deficits in parental bonding have been found to predict both depression and anxiety (e.g., Blatt and Homann 1992;Grotmol et al 2010;Lima et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly it is unknown whether the core features of parental bonding (i.e., care and overprotection) are associated with distinct affective factors. A number of studies have suggested that a lack of care and heightened overprotection are associated with psychopathology in general (Blatt and Homann 1992;Gladstone and Parker 2005;Ingram et al 1998;Lima et al 2010;Rapee 1997), but with few exceptions, it has yet to be determined whether these dimensions are uniquely associated with the features of depressed or anxious states. Moreover, lack of care and heightened overprotection can characterize either or both maternal or paternal behaviors; maternal and paternal bonding may act independently and may be associated with a unique set of affective factors.…”
Section: Introductionmentioning
confidence: 99%
“…One potential process responsible for the transgenerational conveyance of parentally experienced early-life adversity on offspring's mental health could be parenting style. On one hand, parenting style has repeatedly been found to be associated with offspring psychopathology, such as depression and anxiety (Lima, Mello, & Mari, 2010; Rapee, 1997), schizophrenia (Skagerlind, Perris, & Eisemann, 1996), personality disorders (Giakoumaki et al, 2013), and eating disorders (Tetley, Moghaddam, Dawson, & Rennoldson, 2014). On the other hand, parenting style has also been related to adverse childhood experiences.…”
mentioning
confidence: 99%